PENGARUH IKLIM KERJA, BUDAYA ORGANISASI, DAN KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI KARYAWAN PADA GRAND BALISANI SUITES - Putu Aditya Angga Pradana; I Gusti Ngurah Bagus Gunadi; I Wayan Suarjana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
The purpose of this study is to analyze the effect of work climate, organization culture, and leadership on organizational commitment at Grand Balisani Suites. A sample of 102 people was determined by simple random sampling. Data collection methods used in this research include observation, questionnaires, and documentation study. Data analysis technique in this research is multiple linear regression analysis. The results of the research proved empirically that work climate has positive and significant effect on organizational commitment, organizational culture has positive and significant effect on organizational commitment, and leadership has positive and significant effect on organizational commitment.